(untitled) (Journal of Mechanical Engineering, 2011)
Excessive crankcase dilution of lubricating oil in petrol driven vehicles across Dhaka city have been reported recently. A field survey revealed that, gradual increase in the volume of lubricating oil was experienced irrespective of vehicle model, vehicle age and brand of lubricating oil used. The problem was found to originate from adulteration of fuel, probably with the intention of gaining undue financial benefits, stimulated by the high fuel price. Samples were collected from fuel stations across Dhaka and compared with base fuels collected from Eastern Refinery. Investigation of fuel properties like density, distillation curve and visual colour indicated that, condensates from gas fields in around 15% by volume is being mixed with petrol for adulteration. Heavier components of the condensate is causing high rate of crankcase dilution of the lubricating oil in engines. Such dilution is reducing viscosity of the lubricating oil significantly, which may lead to high rate of engine wear and poor performance. DOI: http://dx.doi.org/10.3329/jme.v41i2.7506